Impaired beta-adrenergic response and decreased L-type calcium current of hypertrophied left ventricular myocytes in postinfarction heart failure - Saraiva,R.M. (2003)
Infarct-induced heart failure is usually associated with cardiac hypertrophy and decreased ß-adrenergic responsiveness. However, conflicting results have been reported concerning the density of L-type calcium current (I Ca(L)), and the mechanisms underlying the decreased ß-adrenergic inotropic response. We determined I Ca(L) density, cytoplasmic calcium ([Ca2+]i) transients, and the effects of ß-adrenergic stimulation (isoproterenol) in a model of postinfarction heart failure in rats. Left ventricular myocytes were obtained by enzymatic digestion 8-10 weeks after infarction. Electrophysiological recordings were obtained using the patch-clamp technique. [Ca2+]i transients were investigated via fura-2 fluorescence. ß-Adrenergic receptor density was determined by [³H]-dihydroalprenolol binding to left ventricle homogenates. Postinfarction myocytes showed a significant 25% reduction in mean I Ca(L) density (5.7 ± 0.28 vs 7.6 ± 0.32 pA/pF) and a 19% reduction in mean peak [Ca2+]i transients (0.13 ± 0.007 vs 0.16 ± 0.009) compared to sham myocytes. The isoproterenol-stimulated increase in I Ca(L) was significantly smaller in postinfarction myocytes (Emax: 63.6 ± 4.3 vs 123.3 ± 0.9% in sham myocytes), but EC50 was not altered. The isoproterenol-stimulated peak amplitude of [Ca2+]i transients was also blunted in postinfarction myocytes. Adenylate cyclase activation through forskolin produced similar I Ca(L) increases in both groups. ß-Adrenergic receptor density was significantly reduced in homogenates from infarcted hearts (Bmax: 93.89 ± 20.22 vs 271.5 ± 31.43 fmol/mg protein in sham myocytes), while Kd values were similar. We conclude that postinfarction myocytes from large infarcts display reduced I Ca(L) density and peak [Ca2+]i transients. The response to ß-adrenergic stimulation was also reduced and was probably related to ß-adrenergic receptor down-regulation and not to changes in adenylate cyclase activity.